Analisa Elemen Multi Arms Pada Filter Band Pass Mikrostrip Menggunakan Resonator Open Loop Pada Extremely High Frequency - M. Reza Hidayat; Difa Dwi Juliantara Sukmawan (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2020)
The use of bandpass filters is commonly used but the use of specifications varies depending on needs, in this case the microstrip bandpass filter is expected to observe the multiarms characteristics of the open loop resonator on the performance of the bandpass filter for EHF frequencies. The design of this microstrip bandpass filter uses a multiarms open loop resonator design where at the beginning of the simulation stage uses only 1 arm with patch width, arm spacing, feeder line width and patch length based on trial and error. The final simulation results are obtained with a connector distance of 2 mm and a distance of 1 mm between arms with a value of S11 = -13.8 dB and S21 = -2.8 dB at a frequency of 30.8 GHz based on the simulation results. The filter has been successfully fabricated but cannot be measured because the frequency is too high and the measuring instrument cannot measure the frequency